(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2025)
Appendicitis is a common surgical emergency, typically presenting with right lower quadrant abdominal pain. However, atypical presentations, such as left-sided appendicitis, pose significant diagnostic challenges, especially in patients with underlying conditions like intestinal malrotation. A 40-year-old female was diagnosed with a left-sided burst appendix, initially diagnosed as peptic ulcer disease. After experiencing severe abdominal pain and distension, the patient underwent a CT scan which revealed free gas under the diaphragm and finally was intraoperatively diagnosed as left-sided burst appendix, complicated by intestinal malrotation. The patient underwent a successful appendectomy and postoperative complications were managed. The case emphasizes the need for differential diagnosis of abdominal pain, particularly left-sided appendicitis, especially in coexisting conditions like intestinal malrotation and calls for comprehensive diagnostic approaches and adaptable surgical management in atypical presentations. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 41-44